Cytokine Profile in Children with Severe Multisystem Inflammatory Syndrome Related to the Coronavirus Disease 2019 - Rodríguez-Rubio, Miguel; Menéndez-Suso, Juan J.; Cámara-Hijón, Carmen; Río-García, Miguel; Laplaza-González, María; Amores-Hernández, Irene; Romero-Gómez, María P.; Álvarez-Rojas, Elena; Salas-Mera, Diana; López-Granados, Eduardo; de la Oliva, Pedro (Journal of Pediatric Intensive Care, 2021)
The multisystem inflammatory syndrome in children (MIS-C) is a novel and concerning entity related to severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection. Although MIS-C has been the subject of intensive research efforts, its pathophysiology and optimal treatment remain elusive. We studied the clinical features, laboratory findings, and immunoinflammatory profiles of seven children prospectively admitted to a pediatric intensive care unit (PICU) during the first wave of the pandemic. All patients had immunoglobulin (Ig)-G against SARS-CoV-2, four of seven patients had both IgM and IgG, and in one of the 7 SARS-CoV-2 was detected in a respiratory sample. All patients received intravenous fluid boluses (median: 15 mL/kg) and norepinephrine. The most common form of respiratory support was supplemental oxygen via nasal cannula. None of the patients needed mechanical ventilation. The cardiovascular system was frequently involved. All patients had an elevated troponin-I (median: 107.3 ng/L). Four out of seven patients had coronary artery abnormalities, and two of seven had both abnormal electrocardiogram (EKG) findings and evidence of left ventricular dysfunction on echocardiogram. Ig levels and complement function were normal. Peripheral blood phenotyping with flow cytometry showed decreased T-cell numbers at the expense of CD8+ T-cells. Cytokine profiling showed a heterogeneous increase in interleukin (IL)-6, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, IL-18, IL-2Ra, IL-10, and IL-1Ra that tended to normalize after treatment. Our study shows that children with MIS-C have elevated plasma levels of pro- and anti-inflammatory cytokines in the acute phase of the disease without other relevant immunologic disturbances. These findings suggest the presence of a mixed antagonist response syndrome (MARS) similar to that present in pediatric sepsis. Combining a meticulous differential diagnosis with cautiously coordinated immunomodulatory therapy and high-quality supportive care can help clinicians avoid causing iatrogenic harm in patients with MIS-C.
Keywords: cytokines; severe acute respiratory syndrome-coronavirus-2; novel coronavirus 2019; MIS-C; shock